(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This study highlights the role of architectural settings as sacred spaces in the ritual practices of the Bayan community in Lombok, Indonesia. The research focuses on three key rituals: Menggawe Menyunat, which signifies human relationships through the coming-of-age ceremony for Bayan boys; Ngaji Makem Ngaturang Ula Kayang, representing human connection with nature as an expression of gratitude for agricultural bounty; and Maulid Adat, symbolizing human bonds with God during the commemoration of Prophet Muhammad’s birth. Using a qualitative case study approach, the research integrates field observations, in-depth interviews, and literature analysis to reveal the function, hierarchy, and transformation of ritual spaces such as Masjid Kuno Bayan Beleq, traditional houses, and the sacred pathway Rurung Agung. The findings demonstrate that these architectural settings are not merely venues for rituals but embody the spiritual, cultural, and ecological symbolism of the Bayan community. This article contributes to the discourse on sacred architecture and the preservation of traditional culture amidst modern challenges.